Prior appendectomy and cerebral infarction as potential risk factors for recurrent ischemic colitis: A retrospective observational study - Tomohiro Takatsu; Noboru Misawa; Tsutomu Yoshihara; Keiichi Ashikari; Takaomi Kessoku; Hidenori Ohkubo; Kunihiro Hosono; Masato Yoneda; Satoru Saito; Atsushi Nakajima; Takuma Higurashi (JGH Open, 2023)
Abstract Background and Aim Ischemic colitis (IC) is a benign disease associated with acute lower gastrointestinal bleeding and frequent recurrence. While several studies have investigated risk factors for IC onset, few have assessed the risk factors for recurrent IC. This study aimed to identify risk factors for recurrent IC. Methods Potential risk factors for recurrence were assessed by examining medical records and laboratory findings in this single‐center retrospective study. We extracted the following data from the patients' medical records: patient characteristics, clinical signs and symptoms, laboratory findings, method of treatment, length of hospital stay, disease course, and the frequency of IC morbidities. Patients with IC were selected from a total of 439 312 patients over an 11‐year period. Patients were divided into recurrent and nonrecurrent IC groups. Results In total, 225 patients met the diagnostic criteria for IC during the specified study period; of these, 204 patients (90.7%) and 21 patients (9.3%) were included in the nonrecurrent and recurrent IC groups, respectively. Univariate and multivariate analyses showed a significant association between IC recurrence and both cerebral infarction (P = 0.008, odds ratio [OR] = 6.3) and history of appendectomy (P = 0.0005, OR = 6.2). The median (interquartile range [IQR]) follow‐up time for all patients was 1556 (353–2768) days; this was much longer than the median (IQR) time to recurrence of 291 (64–907) days in the recurrent IC group. Conclusion The results of this study suggest that prior cerebral infarction and appendicectomy may be risk factors for IC recurrence.